Evolutionary computation in gene regulatory network research - Iba, Hitoshi; Noman, Nasimul (Hoboken, New Jersey : Wiley, 2016)
"This book is a step-by-step guideline for research in gene regulatory networks (GRN) using evolutionary computation (EC)"--
Includes bibliographical references and index.
Keywords: Genetic regulation -- Mathematical models; Gene regulatory networks -- Computer simulation; Genetic algorithms; Evolutionary computation; COMPUTERS / Programming / Algorithms; COMPUTERS / Bioinformatics; COMPUTERS / Database Management / Data Mining